Effect of soil solarization and some mulching to control southern blight (Sclerotium rolfsii Sacc.) of pepper in Marmara region - Zühtü POLAT; Gülay BEŞİRLİ; İbrahim SÖNMEZ; Yasin ÖZDEMİR (Derim, 2017)
Soil-borne diseases cause significant yield losses in vegetable production. The study was carried out to determine the effect of some mulches materials and solarization application on southern blight (Sclerotium rolfsii) on Yalova Yaglik 28 pepper cultivar. The trial was conducted in the organic agricultural parcels belonging to Atatürk Central Horticultural Research Institute in Yalova, in 2011-2014. Solarization application was made for 8 weeks, using 0.025 mm in thickness transparent polyethylene cover in 2011 and 2013’s July and August. Under solarization, soil temperature at 5 cm depth was determined as 47-50°C with increasing 8-12°C compared to control. The application of soil solarization on the disease evaluated in both years was found to be effective by 55.0%-73.0%. The white Tyvek mulch applications showed inconsistency results between two years. Black polyethylene mulch application was ineffective in suppressing the disease in both years. Based on these results, soil solarization can be recommended to control Sclerotium rolfsii disease in field in Marmara region.